STUDI LITERATUR : PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL BERBASIS SMART APPS CREATOR PADA MATA PELAJARAN INFORMATIKA UNTUKMENINGKATKAN KEMAMPUAN BERPIKIR KOMPUTASIONAL PESERTA DIDIK SMAN 5 SURAKARTA - Joko Sarono; Triana Rejekiningsih, Akhmad Arif Musadad (Prosiding Seminar Nasional Indonesia, 2024)
In an era of ever-developing information technology, education requires innovative approaches to optimize learning and equip students with relevant skills in the digital world. Smart Apps Creator-based digital learning materials provide engaging and interactive tools for IT learning. By using this technology, educators can create learning applications that are tailored to students' needs and interests. This allows for more personalized learning and increases student involvement in the teaching and learning process. Informatics subjects play an important role in developing students' computational thinking skills, such as problem solving, logic, algorithms and modeling. With digital learning materials based on Smart Apps Creator, the use of learning media at SMAN 5 Surakarta is still dominated by print media, namely textbooks, resulting in students lacking enthusiasm in the teaching and learning process in informatics subjects. This research uses 4D modeling (define, design, development, disseminate). The trial was carried out involving 72 class X students. Consisting of class X-E9 with 36 students, class X-E10 with 36 students. The research results show that the feasibility of the product from the evaluation results of material experts is 96%, media experts 91%, which includes the "Very Valid" criteria, while the teacher response evaluation results are 95% and are included in the "Very Good" criteria. Furthermore, a trial was carried out with 95% of student responses which fell into the "Very Good" criteria so that it could be concluded that the Smart Apps Creator-based learning media for informatics subjects was suitable for use in the learning process.